Programa Escola Ativa: análise histórica sobre a política pública voltada para as classes multisseriadas nas escolas do campo de Sergipe - Santana, Geneluça Cruz (2022)
This research analyzed the Programa Escola Ativa (Active School Program) that was directed to the multigrade classes of rural schools. The main objective was to historically analyze the Active School Program as a public policy aimed at the multigrade classes in the State of Sergipe, in Brazil, between 1997 and 2012. As specific objectives we aimed to: highlight the historical process of struggle of social movements and the construction of the conception of Rural Education; identify public policies for Rural Education directed to the multigrade classes; identify the formative process aimed at multiplying teachers who worked with the pea; and to reflect the contributions of the Active School Program for Rural Education. Our initial hypothesis pointed out that the Active School Program was implemented in the multigrade classes of rural schools, but it failed to break with an old-fashioned kind of rural education and never met the needs and specificities of a Global Rural Education. To achieve our goals, we seek to appropriate the method of dialectical historical materialism, in order to produce knowledge from the concrete reality of the object in its historical process of existence. The categories: totality, dialectics and contradiction were used in the construction of the historical knowledge of society, as a space of fights and class struggles. This is a qualitative research, built from bibliographic research, documentary analysis and interviews with four teachers who worked in the classroom with the Active School Program, two supervisors and two teachers who maintained a critical posture in relation to the program. As a theoretical reference we use Martins (2008) and Tonet (2016) bringing their contributions on the method of historical-dialectical materialism; Arroyo (2012, 2009, 2007) and Caldart (2012, 2008, 2004, 2002) for Rural Education and Hage (2011, 2010) for the multigrade classes. As a result, we conclude that the Escola Ativa Program had and made available a continuing education structure for multiplier teachers that should reach teachers who worked in the classroom, which did not occur as it should. After the reformulation, the referred program contributed to lead the multiplier teachers to discuss Rural Education, but continued to contribute to the maintenance of rural education, since the struggles and constructions carried out by social movements were included in the theoretical structure of the program, but not were implemented in everyday school practice.